Dendrochronology of sessile oak (Quercus petraea) on the transition between the sub-Mediterranean and temperate Continental climatic zones in Slovenia - Saražin, Jaša (Les (Ljubljana), 2018)
A local tree-ring chronology of sessile oak (Qercus petraea) was constructed for the site Klanec pri Kozini (KLA), Slovenia (45.59° N, 13.92° E, 450 m a.) located on the Karst edge on the transition from the sub-Mediterranean climatic to temperate Continental zones. The chronology is 93 years long and covers the period 1925-2017. A comparison with four local oak chronologies from Slovenia and 38 from the surrounding countries (distance 65-220 km) showed that KLA agreed best with the local oak chronology of Rožnik, Ljubljana (ROZ), and two other oak chronologies from central Slovenia (the surroundings of Novo mesto and Ljubljana), one from Croatia and one from Austria. Dendroclimatological analysis showed that the main factor affecting tree-ring variation is June temperature (negative effect) and March precipitation (positive effect), which to a great extent explain the relation to other chronologies. The negative effect of June (maximal) temperature has become increasingly significant in the last few decades, which can be ascribed to warming related to ongoing climatic change.
Keywords: climate change; Croatian Growth; dendrochronology; dendroclimatology; dendroklimatologija; dendrokronologija; hrast; klimatske spremembe; Kozina; les; oak; ree-rings; širina branik; teleconnection; telekonekcija; wood